Solid Waste Management in Jogja Hospital - Muchsin Maulana; Hari Kusnanto; Agus Suwarni (International Journal of Public Health Science (IJPHS), 2016)
There are some groups who may get the risks of hospital waste disposal. The first group is the patients who come to hospital to get cure and care. It is the most vulnerable group. The second is hospital’s employees who have direct contact with the patients as main illness’s agents on doing their daily duties. The third group is the visitor or those who accompany the patients; their risk is big as well. The last group is the society, people who live near the hospital, even when the waste siposal is done inappropriately. It causes the decrease of environmental quality which leads to the decline of health quality in the area. Hence, hospital has a responsibility to manage the disposal process of waste correctly and appropriately by conducting sanitation programs in hospital. Jogja Hospital is a Government-owned Hospital run by the Government of city of Jogyakarta. In its daily activities, the hospital produces waste which, if not properly discharged or burned, may cause adverse effect on workers as well as the surrounding area. Jogja hospital has Incinerator, thus simplifying the management such waste. The waste management including the rules, procedures and policymaking need to be explored to investigate the process of waste management of Jogja hospital.